763 Feasibility and reliability of a comprehensive three-dimensional transesophageal echocardiography screening process for transcatheter mitral valve replacement. (8th December 2021) - Piroli, Francesco; Boccellino, Antonio; Ingallina, Giacomo; Rolando, Marco; Melillo, Francesco; Ancona, Francesco; Stella, Stefano; Biondi, Federico; Denti, Paolo; Castiglioni, Alessandro; Agricola, Eustachio
Abstract: Aims: The planning of transcatheter mitral valve replacement (TMVR) requires cardiac imaging assessment to establish patient eligibility according to mitral valve anatomy, device characteristics and risk of left ventricular outflow tract (LVOT) obstruction. In this setting, computed tomography (CT) is considered the reference method. Although recent studies demonstrated that three-dimensional transesophageal echocardiographic (3D-TEE) assessment of mitral anatomy presents a good agreement compared to CT, its potential role in the TMVR planning has never been fully evaluated. To test feasibility and reliability of a comprehensive 3D-TEE screening in candidates for TMVR. Methods: We performed a single-centre retrospective observational study including 59 consecutive patients referred to our centre for TMVR due to high surgical risk, who performed a pre procedural CT and 3D-TEE screening. The measurements of mitral annulus (MA), native LVOT and predicted Neo-LVOT, assessed with CT and 3D-TEE were collected in order to evaluate their concordance in the assessment of TMVR eligibility. The final suitability decision was given by the valve manufacturer based on CT measurements and then compared with the screening results obtained with 3D-TEE evaluation. 3D-TEE measurements were obtained with a post processing analysis using a novel automated software platform (3mensio Structural Heart 10.1 - 3mSH, Pie Medical Imaging, Bilthoven, Netherlands). Results: Excellent correlation was found between 3D-TEE and CT measurements for MA area ( r =0.85), antero-posterior diameters ( r = 0.81), native LVOT ( r =0.82) and Neo-LVOT areas ( r =0.95) (all P -values <0.0001). Among 59 patients screened, 17 did not undergo the intervention because were found ineligible due to small predicted neo-LVOT, too small or too large MA area. Among the 42 patients with a successful screening, 32 underwent TMVR and all of them showed a correct implantation and no LVOT obstruction at post procedural echocardiographic evaluation. An almost perfect agreement among CT and 3D-TEE was found in assessing the eligibility for TMVR implantation (Cohen kappa 0.82, P <0.001). Interobserver and intraobserver agreements were found excellent for the parameters appraised with ICCs >0.80. Conclusions: 3D-TEE appraisements of MA dimensions, native LVOT and Neo-LVOT are feasible in patients candidate for TMVR, showing good correlations with CT measurements and high accuracy to predict TMVR screening success.